Metabolites replace the parent drug in the drug arena. The cases of fonazepam and nifoxipam - Katselou, Maria (Forensic Toxicol, 2016)
Fonazepam (desmethylflunitrazepam) and nifoxipam (3-hydroxy-desmethylflunitrazepam) are benzodiazepine derivatives and active metabolites of flunitrazepam. They recently invaded the drug arena as substances of abuse and alerted the forensic community after being seized in powder and tablet forms in Europe between 2014 and 2016. A review of all the existing knowledge of fonazepam and nifoxipam is reported, concerning their chemistry, synthesis, pharmacology and toxicology, prevalence/use, biotransformation and their analysis in biological samples. To our knowledge, fonazepam and nifoxipam-related intoxications, lethal or not, have not been reported in the scientific literature. All the available information was gathered through a detailed search of PubMed and the World Wide Web.